Knowledge and Attitude of Primary School Pupils Towards Menstrual Hygiene Management - Azeez Arisekola SALMAN; Adetayo Omotolani Adedoyin (Universitas Pendidikan Ganesha, 2025)
This research is motivated by the low knowledge and practice of menstrual hygiene management (MHM) among elementary school students, especially in rural areas that face limited information, facilities, and social support. The purpose of this study was to analyze the level of knowledge and attitudes of primary school students in Moro Local Government Area, Kwara State, Nigeria towards MHM as well as identify differences based on gender. The subjects of this study are upper-class elementary school students in the region. The research method used is quantitative descriptive with a survey approach. The data collection technique was carried out through the dissemination of structured questionnaires containing indicators of knowledge and attitudes towards menstrual hygiene. The data obtained were analyzed using descriptive statistics to illustrate general trends, as well as an independent t-test at a significance level of 0.05 to test differences by gender. The results showed that the level of students' knowledge of MHM was still low, but most had positive attitudes towards menstrual management, and there was no significant difference between male and female students in both knowledge and attitudes, indicating the need for educational interventions and inclusive policies in reproductive health education in primary schools.